2018
DOI: 10.1080/09593985.2018.1492657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kinesio taping on neuromuscular performance and pain of individuals affected by patellofemoral pain: A randomized controlled trial

Abstract: Patellofemoral pain (PFP) is one of the most frequent musculoskeletal dysfunctions in the knee and its treatment is controversial. This study analyzed the effects of Kinesio Taping (KT) immediately and 72 hours after its application on the electromyographic (EMG) activity of the vastus medialis oblique (VMO) muscle, on the isokinetic performance of the quadriceps femoris and on the pain of subjects with PFP. Fifty-four participants were divided into three groups and performed one of the following protocols: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…VMO and VL activity did not change after taping for 0.5 or 1 h. The finding partly supports the results of previous studies where no significant difference was observed after taping 24 or 48 h (Lins et al, 2016). This study also supported other recent studies indicating that the stimulation of KT cannot activate quadricep activity (Lins et al, 2013;Oliveira et al, 2016;Serrao et al, 2016;Melo et al, 2018). However, our findings contradicted the data presented by Watanabe et al (Herrington et al, 2005;Watanabe, 2019), who proposed that the surface EMG amplitude of the VL muscle decreased and the application of a tape may decrease the neuromuscular activation of the knee extensor muscles in healthy runners.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…VMO and VL activity did not change after taping for 0.5 or 1 h. The finding partly supports the results of previous studies where no significant difference was observed after taping 24 or 48 h (Lins et al, 2016). This study also supported other recent studies indicating that the stimulation of KT cannot activate quadricep activity (Lins et al, 2013;Oliveira et al, 2016;Serrao et al, 2016;Melo et al, 2018). However, our findings contradicted the data presented by Watanabe et al (Herrington et al, 2005;Watanabe, 2019), who proposed that the surface EMG amplitude of the VL muscle decreased and the application of a tape may decrease the neuromuscular activation of the knee extensor muscles in healthy runners.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the elasticity of the KT may gradually decrease and even persist for a long time but cannot impose any effect on knee joint. The results are partly identical with those of Melo et al (2018) and Lins et al (2016), who showed that KT cannot alter muscle strength during the knee extension process after taping for 0 or 72 h compared with NT. Given that the studies in the current literature mainly explored the effect of KT within 24 or 48 h, the short time effects of KT should be studied specifically.…”
Section: Discussionsupporting
confidence: 87%
“…The principal investigator has over 17 years of clinical experience in the evaluation and treatment of patellofemoral pain at the time of this study. The Kinesiotaping Association established guidelines for preparing the area for taping were followed [14]. A combination of two taping techniques was used for mechanical correction.…”
Section: Interventionmentioning
confidence: 99%
“…The tape could be applied directly on the skin and left for several days with good adherence and low risk of skin irritation, providing the possibility for a large variety of therapeutic applications. [9][10][11][12] Dr Kenso Kase suggested that, depending on the used application technique, KT can provide therapeutic effects, such as pain and edema reduction, mechanical correction or support, improvement of muscular activity, correction of joint misalignment, and functional, proprioceptive stimulation. 12 The KT method has been studied and researched extensively by both clinicians and researchers as a possible tool in the field of medicine and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%